2014
DOI: 10.1177/1460458214523153
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone–based clinical guidance for rural health providers in India

Abstract: There are few tried and tested mobile technology applications to enhance and standardize the quality of health care by frontline rural health providers in low-resource settings. We developed a media-rich, mobile phone-based clinical guidance system for management of fevers, diarrhoeas and respiratory problems by rural health providers. Using a randomized control design, we field tested this application with 16 rural health providers and 128 patients at two rural/tribal sites in Tamil Nadu, Southern India. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…These include maternal and child health services, tuberculosis treatment services and anti retroviral therapy adherence programs. Many studies in India, have reported mobile phone communication as an effective and acceptable tool in management of diseases such as Type-2 diabetes, tuberculosis, epilepsy and HIV for both patients and health care providers (Ramachandran et al, 2013;Elangovan and Arulchelvan, 2013;Bigelow et al, 2013;Shetty et al, 2011;Bali and Singh, 2007;Gautham et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…These include maternal and child health services, tuberculosis treatment services and anti retroviral therapy adherence programs. Many studies in India, have reported mobile phone communication as an effective and acceptable tool in management of diseases such as Type-2 diabetes, tuberculosis, epilepsy and HIV for both patients and health care providers (Ramachandran et al, 2013;Elangovan and Arulchelvan, 2013;Bigelow et al, 2013;Shetty et al, 2011;Bali and Singh, 2007;Gautham et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Some examples include the use of mobile phone–based guidance for rural health providers in Tamil Nadu, India [14], and the use of a gestational diabetes app by pregnant women in Oxford, United Kingdom [15]. Moreover, it has been documented not only in young adults [16], but also in older adults—both had a high degree of acceptance of apps that promoted physical activity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have concentrated their efforts in improving their interventions prior to evaluating the acceptability (23,24) and others investigated the acceptability of mHealth interventions demonstrating positive results (25)(26)(27)(28). Each of these studies evaluated interventions other than smartphone applications, such as short messaging service (SMS), telecommunication interfaces as well as ehealth interventions emphasizing protocol compliance and treatment adherence respectively.…”
Section: Previous Mhealth Interventionsmentioning
confidence: 99%
“…Authors reported lack of knowledge to be the biggest limitation regarding the mHealth intervention. This impeded proper assessment of the application, as participants did not feel comfortable using it (25)(26)(27)(28). Based on a systematic review conducted by Gagnon et al, most mHealth studies evaluating acceptability of smartphone applications have been conducted amongst health care professionals such as nurses, pharmacists and health workers (18).…”
Section: Previous Mhealth Interventionsmentioning
confidence: 99%